Influence of Ascorbic acid on the Quality of Wheat and Soybean based Breads - Okorie, S. U; Anyanwu, M. O; Ekwe, C. C (Global Journal of Plant and Soil Sciences, 2022)
The work assessed the influence of ascorbic acid on the proximate composition, physical and sensory attributes of wheat and soybean based breads. The samples used in the work were WAF (Wheat/0.00g Ascorbic acid), WSA1 (Wheat / Soybean / 0.10g Ascorbic acid), WSA2 (Wheat / Soybean / 0.15g Ascorbic acid), WSA3 (Wheat / Soybean / 0.20g Ascorbic acid), WSA4 (Wheat / Soybean / 0.25g Ascorbic acid), and WSA5 (Wheat / Soybean / 0.30g Ascorbic acid). The proximate analysis revealed that protein, fat, crude fibre, ash and moisture content increased as the level of ascorbic acid increased. The result also indicated that protein increased from 8.76% to 14.30%, fat (10.77 – 14.74%), crude fibre (1.36 – 2.54%), ash (1.48 – 2.76%) and moisture content (31.52 – 35.15%) respectively. However, there was a decrease (46.11 – 30.51%) in the carbohydrate content. The thiobarbituric acid (TCA) values of the bread increased sharply at ambient temperature (280C) as the storage days increased while the TBA values increased gradually at freezing (-140C) and refrigeration (100C) temperatures until the 14 th (last) day. The sensory evaluation indicated that the breads with less than 0.25g ascorbic acid were more acceptable organoletpically than those containing above 0.25g ascorbic acid.